OPTICAL MICROSCOPY AND SEM FOR IDENTIFYING CLOGGING MATERIAL IN A DRIP IRRIGATION SYSTEM - Ribeiro, Maycon Diego (2018)
The aim of this study was to apply optical microscopy and scanning electron microscopy (SEM) techniques to identify and assess dripper clogging of an irrigation system. Three dripper models (Taldrip, Streamline, and Tiran) underwent 1200 hours of irrigation with three types of effluents: treated domestic wastewater, water with a high calcium content, and urban water supply. Samples of the material adhered to the inside of drippers were analyzed by means of the smear method aiming at their biological identification. Other samples were taken to obtain SEM images. The presence of algae, bacteria, and biological components of biofilm was observed in drippers operating with wastewater and water with calcium, this latter in a low number. The formation of biofilm and chemical precipitates of calcium were observed in SEM images, leading to emitter clogging. Optical microscopy and SEM analyses allowed identifying the degree of fouling by biofilm and chemical precipitates in dripper clogging.